Age-based demographic and reproductive assessment of orangespine Naso lituratus and bluespine Naso unicornis unicornfishes - Taylor, B.; Rhodes, K.; Marshell, A.; McIlwain, Jennifer (Blackwell Publishing, 2014)
Bluespine unicornfish Naso unicornis and orangespine unicornfish Naso lituratus were sampled in Pohnpei and Guam, Micronesia, over 13 months to identify reproductive and age-based demographic features necessary for informed management. Age and reproductive information were derived from analysis of sagittal otoliths and gonads. Both species had moderate life spans [maximum ages of 23 (N. unicornis) and 14 years (N. lituratus)] compared with published estimates of conspecifics from other locations (>30 years) and of other Naso species. Length at maturation for N. unicornis was similar between Pohnpei and Guam while females consistently matured at a larger size [c. 30 cm fork length (LF)] than males (c. 27 cm LF). This sex-specific pattern was reversed in N. lituratus for which estimates of maturation length (females: 15 cm LF; males: 18 cm LF) were only obtained from Guam. Developmental patterns in female gonads of both species suggested that initiation of maturation occurs very early. Growth patterns of N. lituratus displayed rapid asymptotic growth compared with N. unicornis and other congeners as well as slight sex-specific patterns of length-at-age. Results highlight the considerable spatial variation that may occur in the population biology of these species across various scales. Additionally, proper management remains complicated without improved knowledge of fishery trends and reproductive behaviour in unicornfishes, species that are prime fishery targets in Micronesia and elsewhere.